The Role of Cathepsins in Memory Functions and the Pathophysiology of Psychiatric Disorders - Niemeyer, Christine; Matosin, Natalie; Kaul, Dominic; Philipsen, Alexandra; Gassen, Nils C. (Frontiers in Psychiatry, 2020)
Cathepsins are proteases with functions in cellular homeostasis, lysosomal degradation and autophagy. Their role in the development of neurodegenerative diseases has been extensively studied. It is well established that impairment of proper cathepsin function plays a crucial role in the pathophysiology of neurodegenerative diseases, and in recent years a role for cathepsins in mental disorders has emerged given involvement of cathepsins in memory function, hyperactivity, and in depression- and anxiety-like behavior. Here we review putative cathepsin functions with a special focus on their role in the pathophysiology of psychiatric diseases. Specifically, cathepsins are crucial for maintaining cellular homeostasis, particularly as strategy to acute stress response. Disruption can lead to psychiatric diseases. Specifically, cathepsins can be excreted via a process called secretory autophagy. Thereby, they are able to regulate extracellular factors such as brain-derived neurotrophic factor and perlecan c-terminal fragment LG3 providing maintenance of neuronal homeostasis and mediating neuronal plasticity in response to acute stress or trauma. In addition, impairment of proper cathepsin function can result in impaired synaptic transmission by compromised recycling and biogenesis of synaptic vesicles. Taken together, further investigations on cathepsin functions and stress response, neuroplasticity, and synaptic transmission will be of great interest in understanding the pathophysiology of psychiatric disorders.